2012
DOI: 10.1007/s10856-012-4599-1
|View full text |Cite
|
Sign up to set email alerts
|

Local inhibition of angiogenesis by halofuginone coated silicone materials

Abstract: Anti-angiogenic therapy is a promising approach for the treatment of increased angiogenesis in certain diseases. We aimed to investigate the local anti-angiogenic effect of silicone implants coated with Halofuginone, an angiogenesis inhibitor that inhibits synthesis of collagen-type-I and matrix metalloproteinases. The degree of angiogenesis was observed after implantation of surface modified Halofuginone eluting silicone implants into a submuscular pocket in rats over a period of 3 months. Subsequently, key m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 43 publications
2
5
0
Order By: Relevance
“…In the leukemia mouse model, we did observe increased gene expression of VEGF, HIF-1α and ANGPT-2, which were significantly reduced after HF treatment. These PCR data support that HF antiangiogenic effect implicates multiple targets, as demonstrated by Jordan ans Zeplin [ 25 ], MMP-2, bFGF and TGF-β were down-modulated by HF in physiologic conditions.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In the leukemia mouse model, we did observe increased gene expression of VEGF, HIF-1α and ANGPT-2, which were significantly reduced after HF treatment. These PCR data support that HF antiangiogenic effect implicates multiple targets, as demonstrated by Jordan ans Zeplin [ 25 ], MMP-2, bFGF and TGF-β were down-modulated by HF in physiologic conditions.…”
Section: Discussionsupporting
confidence: 84%
“…Jordan and Zeplin, showed that HF significantly reduces the gene expression of pro-angiogenic factors in physiologic conditions in muscle cells [ 25 ]. In order to evaluate the effect of HF in leukemic cells, we treated the APL cell line NB4 and performed a screening of gene expression using the PCR array method analyzing 84 predefined genes involved in angiogenesis (Additional file 2 : Table S2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Upregulation of Egr1 and Egr-2 was observed at 1-5 and 3 h, respectively, followed by a marked decrease thereafter. 4) and in a recent study evaluating the antiangiogenic effect of halofuginone [46]. Expression of MMP-2 and TIMP-2 was downregulated after 8 h of halufuginone treatment, whereas that of heparanase (HPSE) and TIMP-1 was unaffected.…”
Section: Discussionmentioning
confidence: 89%
“…It has been reported that HLF may induce apoptosis and reduce cancer volume in experimentally induced colon cancer in the nude mouse (Chen et al, 2015). It may also have antiangiogenic, antimetastatic and antiproliferative effects, increase apoptosis/necrosis, and decrease collagen content in other cancer types (Gavish et al, 2002;Grudzien et al, 2010;Jordan and Zeplin, 2012). Further, HLF may enhance the effects of chemotherapeutic agents on cancer (Leiba et al, 2012).…”
Section: Resultsmentioning
confidence: 99%